Sigortacılığa Giriş - Şuayipoğlu, Melda; Tanilyan Sürer, Tilda; Diker, Fevzi; Taşcı, Mehmet Zafer; Poyraz Can, Sema; Medetoğlu, Batuhan; Er, Hülya; Şentürk, Ömer; Yılmaz, Mehmet Arda; Kahramanoğlu, Ali; Özcan, Hakan (Akademisyen Yayınevi Kitap DOI Portalı, 2024)
-